The influence of price, product quality, product review on purchase intention framelessplate - Kautsar, Mohamad; Pasaribu, Lamhot (Institute of Computer Science (IOCS), 2024)
The goal of this research is to evaluate the effect of price, quality, and reviews of products on purchase intention of Jabodetabek, Indonesia’s Framelessplate consumers in the automotive accessories market. Data were collected from a sample of 99 respondents through a questionnaire which was developed digitally and analyzed by Partial Least Squares (PLS). The results show that both product quality and product reviews are important factors when consumers make purchasing decisions, as these factors have a strong and positive influence on their purchase intentions. On the other hand, it was also found that price does not have a significant effect on purchase intention, meaning it might be positively affected with other factors. This study enhances understanding of consumer behavior with regards to e-business with specific emphasis on the qualitative aspects of the study, reviews & product quality which are key purchase determinants in the automotive accessories environment.